2009
DOI: 10.1387/ijdb.072427jb
|View full text |Cite
|
Sign up to set email alerts
|

A history of Evo-Devo research in Spain

Abstract: A history of Evolutionary Developmental Biology (Evo-Devo in short) in Spain is presented. From an almost total lack of research and tradition in Embryology, Genetics and Evolution throughout the 19 th and well into the 20 th century, evolution and development was first bridged in the 1970-80s by the structuralist approach of Pere Alberch and by important sidestudies from the Madrid School of Developmental Genetics. A second stage was set in the early 1990s when a few scattered labs start to address problems w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 98 publications
0
3
0
Order By: Relevance
“…Baguñà (2009) has nicely summarized major steps in these areas from the time of the Dahlem conference to the present, starting with the discovery of the homeobox, the recognition that regulatory systems are widely conserved across taxa, the discovery of the important role of gene duplication in vertebrate phylogeny, the findings that cis-regulatory modules evolve by mutation, co-option and reshuffling, the understanding that there is a kind of molecular toolbox for development, the formulation of the concept of gene regulatory networks, sequencing of whole genomes, and the dawn of the age of genomics, and subsequently phylogenomics. While I think I made some progress after the Dahlem conference , homoplasy remains a challenge today.…”
Section: Homoplasy-a Key Concept In Evo-devo Researchmentioning
confidence: 99%
“…Baguñà (2009) has nicely summarized major steps in these areas from the time of the Dahlem conference to the present, starting with the discovery of the homeobox, the recognition that regulatory systems are widely conserved across taxa, the discovery of the important role of gene duplication in vertebrate phylogeny, the findings that cis-regulatory modules evolve by mutation, co-option and reshuffling, the understanding that there is a kind of molecular toolbox for development, the formulation of the concept of gene regulatory networks, sequencing of whole genomes, and the dawn of the age of genomics, and subsequently phylogenomics. While I think I made some progress after the Dahlem conference , homoplasy remains a challenge today.…”
Section: Homoplasy-a Key Concept In Evo-devo Researchmentioning
confidence: 99%
“…It has been suggested that in the period between the 50s and the 80s, Spain was a desert for Genetics with an oasis centered in the group of García-Bellido in Madrid (Baguña, 2009). Unless one was interested in plant genetics, there is some truth to this view, but it is also true that Genetics was taught and worked upon in other places, and that these smaller activities had an influence on some individuals.…”
Section: Outside Madridmentioning
confidence: 99%
“…They have been fascinating scientists from different working fields for more than a century. After nearly half a century of complete separation between embryological and evolutionary studies, the two fields converged in the late 1970s-early 1980s, giving rise to the "EvoDevo" research field (Alberch, Gould, Oster, & Wake, 1979;Bonner, 1982;Gould, 1977; for reviews, see Amundson, 2005;Baguna, 2009). These pioneer Evo-Devo studies urged to uncover the generative rules of development, that is, the set of principles that connect all hierarchical scales of development together: molecules, cells, tissues, and organs.…”
Section: Introductionmentioning
confidence: 99%